A Subunit Vaccine Harboring the Fusion Capsid Proteins of Porcine Circovirus Types 2, 3, and 4 Induces Protective Immune Responses in a Mouse Model - Qikai Wang; Ran Zhang; Yue Wang; Ying Wang; Libin Liang; Haili Ma; Haidong Wang; Longlong Si; Xingchen Wu (Viruses)
Coinfections with porcine circovirus types 2, 3, and 4 (PCV2, PCV3, and PCV4) are increasingly being detected in the swine industry. However, there is no commercially available vaccine which prevents coinfection with PCV2, PCV3, and PCV4. The development of a vaccine expressing capsid (Cap) fusion proteins of multiple PCVs represents a promising approach for broadly preventing infection with PCVs. In this study, we developed a PCV subunit vaccine candidate (Cap 2-3-4) by predicting, screening, and fusing antigenic epitopes of Cap proteins of PCV2, PCV3, and PCV4. Immunoprotection assays showed that the prokaryotic expression of Cap 2-3-4 could effectively induce high levels of PCV2, PCV3, and PCV4 Cap-specific antibodies and successfully neutralize both PCV2 and PCV3. Furthermore, Cap 2-3-4 demonstrated a potent ability to activate cellular immunity and thus prevent lung damage in mice. This study provides a new option for the development of broad vaccines against PCVs.